Socio-Demographic Determinants of School Indiscipline - Kompirović, Tatjana P.; Dančetović, Nikola N.; Radojević, Tatjana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The paper examines the correlation between students’ indiscipline in schools and some socio-demographic variables. The aim of the research is to investigate the connection of school indiscipline with the gender of students, their age, academic success and the number of unexcused absences, the birth order and the number of children in the family, the employment of parents and their educational background. The sample consisted of students of both sexes, aged 11 to 14 (N = 130), i.e. students of V (N = 30), VI (N = 48), VII (N = 22) and VIII (N = 30) grade. Basic Data Questionnaire and The Scale of School Discipline were used in the research. The data were processed using Correlation Analysis, T-test, and Variance Analysis. The obtained results showed that there is a positive correlation of school indiscipline with the age of students, school, academic success of students, and the education of parents.